Framing Cosmetic Purchase Decisions in the Digital Era: The Role of Influencer Storytelling and Consumer Reviews with Self Brand Connection as a Moderating Variable - Sudjaniah, Derah; Sascha, Indira; Arita, Melva; Yulistiyaningsih, Arum; Siregar , Rio Octogi (International Journal of Social Service and Research, 2025)
This study aims to analyze the influence of influencer storytelling and consumer reviews on cosmetic product purchase decisions, with self-brand connection as a moderating variable. The focus is on cosmetic consumers across Indonesia within the context of digital marketing. The theoretical foundation includes the Theory of Planned Behavior, Elaboration Likelihood Model, and Self-Congruity Theory. A quantitative method using Partial Least Squares–Structural Equation Modeling (PLS-SEM) was employed. The findings reveal that both influencer storytelling and consumer reviews positively affect purchase decisions. Moreover, self-brand connection strengthens the relationship between these variables and purchase decisions, highlighting the emotional role consumers play in shaping brand preference. These findings provide both theoretical and practical implications, especially in crafting effective digital marketing strategies for local cosmetic brands. The study emphasizes the importance of fostering emotional bonds between brands and consumers to enhance loyalty and drive purchase decisions.